Homeownership. Low household mobility, volatile housing prices, high income dispersion - Sven Rady; François Ortalo-Magné (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2002)
We develop a dynamic stochastic equilibrium model of two locations within a city where heterogeneous households make joint location and tenure mode decisions. To investigate the effect of homeownership on equilibrium prices and allocations, we compare the response of this model economy to a labor shock with that of a rental-only version. This comparison yields three results. First, homeownership enables more households to remain in the more desirable location at the expense of newcomers. Second, homeownership adds to the volatility of the housing market. Third, homeownership may amplify the dispersion of household income within a location. Homeownership raises distributional issues. The households who consume the most housing gain the most from the ability to own their home. Newcomers to the city are the main losers.
urn:nbn:de:bvb:19-epub-28-1
Keywords: 330